2011
DOI: 10.5081/jgps.10.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different Interpolation Models Used in Network-RTK for the Virtual Reference Station Technique

Abstract: This paper thoroughly investigates several approaches to implementing the GNSS network-based real-time positioning technique, which requires the estimation of atmospheric corrections on an epoch-by-epoch basis for RTK. In this study, a network of Continuously Operating Reference Stations in New South Wales, known as CORSnet-NSW, was utilised to: 1) obtain atmospheric residuals from each reference station, and 2) determine network correction for a rover operating in the area covered by the network using several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The Real Time Kinematic (RTK) method's positioning accuracy depends on the inter-station distances of the GNSS networks. The troposphere delay error reaches a few cm at distance of 70 km and above between the reference stations [11].…”
Section: Introductionmentioning
confidence: 95%
“…The Real Time Kinematic (RTK) method's positioning accuracy depends on the inter-station distances of the GNSS networks. The troposphere delay error reaches a few cm at distance of 70 km and above between the reference stations [11].…”
Section: Introductionmentioning
confidence: 95%
“…The NRTK positioning is a technology that calculates the correction message suitable for an area where a GPS rover is positioned [2,3]. The calculated correction message is transferred to the rover, to enable highly accurate real-time positioning [4]. Multiple GPS reference stations are utilized, because using a single reference station reduces accuracy if the distance between the rover and the reference station exceeds 10 km [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of numerous comparisons of interpolation model applications in the network solution as presented in e.g. (Dai et al, 2004;Geisler, 2006;Próchniewicz, 2011;Al-Shaery et al, 2011), the Ordinary Kriging Method (OKR) may be indicated as the optimal interpolation method for distancedependent errors in regional network, which is characterized as highly precise in determining correction and makes possible the proper estimation of their variance. Numerical tests on positioning model solutions as presented in this paper applied the OKR method, utilizing the gaussian theoretical variogram model.…”
Section: Application Parameters and Solution Algorithmmentioning
confidence: 99%
“…Distance-Based Linear Interpolation Method (Gao et al, 1997), Linear Combination Model (Han andRizos, 1996, 1997), Linear Interpolation Method (Wanninger, 1995), Low-Order Surface Model (Fotopoulos and Cannon, 2001)) and (ii) the geostatistical methods (e.g. Least-Squares Collocation Method (Marel, 1998;Raquet, 1998), Ordinary Kriging Method (Wielgosz et al, 2003;Al-Shaery et al, 2011)). From among these models, only Distance-Based Linear Interpolation Method does not allow the defining of the predicted values errors.…”
Section: Application Parameters and Solution Algorithmmentioning
confidence: 99%